Isolation of microRNA from conjunctival impression cytology. (March 2015) - Pilson, Qistina; Jefferies, Caroline A.; Gabhann, Joan Ní; Murphy, Conor C.
Abstract: Impression cytology (IC) is an easy and safe technique that has been used in the past for harvesting epithelial cells from the cornea and conjunctiva for various applications including histology, immunohistology and molecular studies. Previous investigations have shown the usage of different types of membranes for the purpose of investigating pathophysiology and staging of diseases. This contributes to a better understanding of ocular surface conditions and helps to provide information for diagnosis, therapeutic options and prognosis. Recently, there has been a shift of focus in research towards understanding the contribution of microRNAs (miRs) to ocular disease. Thus far, impression cytology has been explored for measuring gene expression but not for quantifying miR expression. This study describes how miRs and mRNA can be isolated from conjunctival epithelial cells obtained by impression cytology and determines the optimum membrane and technique for this purpose. The IC technique was optimized using Biopore, Immobilon-P SQ and Millicell Hanging Cell Culture Insert membranes on healthy controls. miRs and mRNAs were isolated from the conjunctival epithelial cells (CEC) obtained and measured. Biopore membrane provided the optimum yield of miRs (38.8 ng/μL ± 10.8) and mRNA (155.3 ng/μL ± 20.1) as well as subjectively found to be best tolerated with minimum discomfort. Appreciable levels of miRs and mRNAs were detected from the CEC from healthy controls, confirming that it is possible to isolate miR and mRNA from CEC. Here, we give a detailed description of the application of conjunctival impression cytology to isolate miRs and the convenience of the technique by using the best membrane available. This method can be readily adopted in both clinical and laboratory settings. This technique will facilitate the measurement of miRs to improve our understanding of the pathogenesis of ocular surface conditions as well as potentially identifying novel therapeutic targets. Highlights: We optimized the impression cytology (IC) technique to isolate microRNA and mRNA. Average yield of microRNA (miR) was optimal using Biopore membrane. Average yield of mRNA was comparable between Biopore membrane and Immobilon-P SQ membrane. Quantification of miR from conjunctival epithelial cell (CEC) is possible using IC. It is also possible to show expression of miR from CEC using IC.